2017
DOI: 10.1177/0310057x1704500514
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Sequelae of Memorable Anaesthetic Drug Errors from the Anaesthetist'S Perspective

Abstract: Drug errors amongst anaesthetists are common. Although there has been previous work on the system factors involved with drug error, there has been little research on the sequelae of a drug error from the anaesthetist's perspective. To clarify this issue, we surveyed anaesthetists regarding their most memorable drug error to identify associated factors and personal sequelae regarding their professional practice after the event. An online survey was sent anonymously to 989 Australian and New Zealand College of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…We also found that most respondents believed that medication errors had no specific time of occurrence. However, Amponash et al[ 22 ] identified more errors occurring during night shifts, and McCawley et al[ 18 ] and Erdmann et al[ 19 ] reported more errors occurring during daytime working hours. One of our key findings is that most respondents reported no patient harm resulting from medication errors, consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also found that most respondents believed that medication errors had no specific time of occurrence. However, Amponash et al[ 22 ] identified more errors occurring during night shifts, and McCawley et al[ 18 ] and Erdmann et al[ 19 ] reported more errors occurring during daytime working hours. One of our key findings is that most respondents reported no patient harm resulting from medication errors, consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Clinicians feel embarrassed, guilty, or blamed after disclosing errors, which might stop them from reporting errors. [ 18 , 32 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations